2011
DOI: 10.1111/j.1532-5415.2011.03628.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Multimodal Geriatric Discharge-Planning Intervention to Prevent Emergency Visits and Rehospitalizations of Older Adults: The Optimization of Medication in AGEd Multicenter Randomized Controlled Trial

Abstract: This intervention was effective in reducing rehospitalizations and ED visits for very elderly participants 3 but not 6 months after their discharge from the AGU. Future research should investigate the effect of this intervention of transitional care in a larger population and in usual acute and subacute geriatric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(151 citation statements)
references
References 48 publications
5
139
2
3
Order By: Relevance
“…This finding seems particularly relevant in light of the promising results of geriatric drug management and reconciliation programs. 26,27 Finally, although it might seem intuitive that a better social support protect toward readmissions, 28,29 we found the opposite effect. This is in line with recent multifactorial intervention programs considering it as a cause of avoidable transfers from nursing homes.…”
Section: Discussioncontrasting
confidence: 54%
“…This finding seems particularly relevant in light of the promising results of geriatric drug management and reconciliation programs. 26,27 Finally, although it might seem intuitive that a better social support protect toward readmissions, 28,29 we found the opposite effect. This is in line with recent multifactorial intervention programs considering it as a cause of avoidable transfers from nursing homes.…”
Section: Discussioncontrasting
confidence: 54%
“…Medication reconciliation during care transitions has demonstrated effectiveness in prevention of serious medication errors in multiple studies. [19,28,29] These qualitative data support findings from the literature. Descriptions of near-miss events due to medication mismanagement demonstrated the patients' awareness of the importance of taking medications correctly.…”
Section: Discussionsupporting
confidence: 75%
“…Providing patients with information that the patients themselves state is of value may be the easiest refinement to a discharge educational tool, although this was surprisingly uncommon. 6,9,10,17,23,33,37 Only 2 studies were found that engaged patients in the initial stage of design of the discharge tool, by incorporating information of interest to them. 23,32 For example, a study testing the impact of a computer-generated written education package on poststroke outcomes designed the information by asking patients to identify which topics they would like to receive information about (along with the amount of information and font size).…”
Section: Total References 4015mentioning
confidence: 99%